A cone beam CT based 3D-assessment of bony forefoot geometry after modified Lapidus arthrodesis. Issue 8 (December 2020) - Scheele, Christian B.; Christel, Simon T.; Fröhlich, Imke; Mehlhorn, Alexander; Walther, Markus; Hörterer, Hubert; Harrasser, Norbert; Kinast, Christian
Highlights: The present work focuses on the assessment of forefoot geometry with Cone Beam CT underweight bearing conditions. Recentering the sesamoids under the first metatarsal head will elevate the second metatarsal head. A rotatory correction of the first metatarsal in the coronal plane can be achieved with the Lapidus-procedure. Abstract: Background: Modified Lapidus arthrodesis (MLA) is a well-established treatment modality for hallux valgus deformities (HVD) associated with instability of the first ray. Although the three-dimensional (3D) nature of HVD has long been recognized, diagnostics still focus on plain radiographs. The objective of this study was to validate 3D Cone Beam CT (CBCT) in the perioperative assessment of HVD with focus on the alignment of the forefoot. Methods: In a prospective clinical study, MLA was performed on 30 patients (25 females, 5 males; mean age: 63.2 years). Pre- and postoperatively standard radiographs and CBCT with full weight-bearing were acquired. For the CBCT based assessment, reproducible criteria have been defined, measured, and correlated with established radiological indicators. Results: Evaluation of standard radiographic parameters (hallux-valgus angle [HVA], intermetatarsal angle 1-2 [IMA 1-2], distal metatarsal articular angle [DMAA], tibial sesamoid position [TSP]) showed significant improvement postoperatively. Comparison of measurements obtained from plain radiographs and CBCT were significantly correlated between both measuring techniques, indicating high reliability. Pronation of the first metatarsal and the sesamoids were significantly reduced by the procedure. Due to this repositioning effect, the second metatarsal head was elevated by 3.1 mm, and the lateral sesamoid was lowered by 3.8 mm. However, there was no correlation between the amount of pronation and conventional radiographic measures. Conclusions: Compared to plain radiographs, CBCT allows a more detailed view of the forefoot alignment in the coronal plain after MLA. MLA was able to recenter the sesamoids under der first metatarsal head and conversely led to elevation of the second metatarsal head.